Simulation of fluid dispersion in ejection devices - Shpak, Maksim; Chepeliuk, Olena; Besarab, I. (My University, 2014)
This article describes how moisturizing of bulk components in the dryer-granulator and equipment for its implementation. An ejection device was proposed and by mathematical modeling its rational structure was proved. It was recommended to implement supply of liquid in the central tube and the air - in the peripheral holes. The use of ejecting spray devices which have a proposed design provides a homogeneous water-air mixture with a uniform velocity and sufficient pressure. В статті розглянуто процес зволоження сипких компонентів у сушарці-грануляторі і обладнання для його реалізації. Запропоновано використовувати ежекційний пристрій і шляхом математичного моделювання обґрунтовано його раціональну конструкцію. Рекомендовано здійснювати подачу рідини у центральну трубку, а повітря – у периферійні отвори. Використання ежекційних розпилюючих пристроїв запропонованої конструкції забезпечує отримання однорідної водо-повітряної суміші з рівномірною швидкістю і достатнім тиском.
Keywords: modeling; ejection; dryer-granulator; моделювання; ежекція; сушарка-гранулятор; моделирование; эжекция; сушилка-гранулятор; кафедра машин і апаратів харчових та фармацевтичних виробництв